2020
DOI: 10.1101/2020.04.21.054098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycomic analysis of host-response reveals high mannose as a key mediator of influenza severity

Abstract: 1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Lectin microarrays, in which a panel of lectins (10s to >100) and other carbohydrate-binding probes (e.g., antibodies) are printed on a solid support, are now routinely used in glycomics [5][6][7]. This high-throughput method has identified glycans involved in a variety of systems from melanoma metastasis to viral host-response [8][9][10]. Although lectins are useful tools, they have suffered from a lack of detailed definition of their binding requirements, which hampers their use analytically.…”
Section: Introductionmentioning
confidence: 99%
“…Lectin microarrays, in which a panel of lectins (10s to >100) and other carbohydrate-binding probes (e.g., antibodies) are printed on a solid support, are now routinely used in glycomics [5][6][7]. This high-throughput method has identified glycans involved in a variety of systems from melanoma metastasis to viral host-response [8][9][10]. Although lectins are useful tools, they have suffered from a lack of detailed definition of their binding requirements, which hampers their use analytically.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, our laboratory analyzed the glycomic response to H1N1pdm09 in an adult ferret population using our lectin microarray technology. 15 We found that the severity was not related to sialic acid levels but, rather, correlated with the expression of high mannose N-glycans. Histology on ferret lungs showed high mannose levels corresponded with alveolar severity and was present throughout the tissue on multiple cell types.…”
Section: Introductionmentioning
confidence: 67%
“…We observed several changes in aged ferrets as a function of infection that did not overlay onto severity. For ease of comparison between the aged and adult host responses, we reanalyzed the lectin microarray data from our adult ferret cohort 15 using PCS as the severity metric. In our previous work, adult ferrets showed an increase in α-2,6 sialylation at early infection time points, with levels returning to baseline by day 8 postinfection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 For influenza, the high-mannose motif on infected host cells guides immune responses leading to the concomitant damage associated with disease severity. 8 Recently, high-mannose glycans have been implicated in supporting cholangiocarcinoma metastasis by enhancing the ability to translocate, invade surrounding basement membrane matrix and migrate through micropores. 9 In all eukaryotic cells, GDP-Man is synthesized in cytosol (Figure 1B), and used in endoplasmic reticulum (ER) to support highly organized mannosylation of dolichols and glycoproteins (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%